PENGARUH PENYALURAN DANA ZAKAT TERHADAP TINGKAT KEMISKINAN DENGAN PENGELOLAAN ZAKAT SEBAGAI VARIABEL INTERVENING PADA BAZNAS KABUPATEN LOMBOK TIMUR: Indonesia - Risma Laely Septiani; Ayub Wijayati Sapta Pradana (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2022)
The Covid-19 pandemic has had many impacts on society, especially in the economic sector. The impact of the pandemic that attacks the economic sector has caused the poverty rate to continue to increase. The distribution of zakat funds is one of the factors that have an influence on reducing poverty, which is inseparable from the zakat management process. Therefore, the purpose of this study is to find out how the distribution of zakat funds affects the level of poverty through zakat management. This study conducted observations at BAZNAS, East Lombok Regency using quantitative methods and path analysis with the Sobel test. From the results of the study, it was found that t count 0454 < t table 0.1654 with a significance value of 0.05 so it can be said that zakat management is not able to mediate the relationship between the distribution of zakat funds to the poverty level.